Keterlibatan sosial di era digital: Dampak gerakan online pada perubahan sosial - Andika, Andika (Maliki Interdisciplinary Journal, 2024)
Social engagement in the digital era is experiencing a significant transformation as a result of developments in information technology and the internet. Online movements are one of the main elements influencing social change in society. This article explains the impact of social engagement in the digital era, with a focus on the contribution of online movements to social change. Online movements allow individuals to engage in a variety of social activities without geographic restrictions, creating virtual spaces that facilitate the exchange of ideas, support, and information. In this context, there are several positive impacts, such as increasing participatory involvement and social awareness. However, online movements also have a negative impact on social change. Increasing disinformation and polarization of opinion are serious challenges that need to be addressed. Additionally, social engagement in the digital era can result in social isolation and increased digital addiction. It is important to manage these negative impacts to create a healthy and productive online environment..